Islamic Perspective on the Concepts of Interaction among Multicultural Society - Mohd Khambali @ Hambali, Khadijah; Mohd Paudzi, Nur Hidayah; Sultan Mohsen Sallam, Abdul Nasser (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
Interaction is an important and necessary action that everyone needs in life. Every human being depends on one another to fulfill their necessary needs. Islam has emphasized interaction through the many revealed verses in the Qur’ān as well as the sunnah of Prophet Muhammad (PBUH). In order to build a positive relationship, many concepts of interaction have been introduced by Islamic scholars specifically as guidance for Muslims that are also universally applicable to the whole nation regardless of different religions and ethnicities. The success in the implementation of these concepts can be proven from the rulings of Prophet Muhammad (PBUH) in Medina. The Constitution of Medina is a great guideline in building a solid united multicultural society. This article aims to explain more on the concepts of interaction according to the Islamic perspective. It also expounds on how this concept significantly impacts creating a peaceful co-existence among multicultural society especially in Malaysia as a multi-adherent society based on tasāmuh, mahabbah, and taʻāmul that underlying the concept of fiqh al-taʻāyush.